Synthesis of combinational logic circuits using genetic algorithms - Reis, Cecília (2019)
This paper proposes a genetic algorithm for designing combinational logic circuits and studies three different case examples: the one-bit full adder, the four-bit parity checker and the two-bit multiplier. The objective of this work is to generate a functional circuit with the minimum number of gates.